Congruence of required, implemented, and expected sanitary conditions of fastfood establishments operating in a Mandaluyong City Mall Food Court - Lapus, Kim R.
The study is a descriptive survey of the fastfood operators, municipal health officers and customers and their perceptions about the required implemented and expected sanitary conditions of fastfoods in terms of compliance to P.D. 856 (Sanitation Code of the Philippines) and to determine if there is a congruence in the required, implemented and expected sanitary conditions of the fastfood establishments included in the study. The methodology for the study consisted of two parts: phase one was about the survey of customers, fastfood personnel, compliance to the sanitation code as evaluated by the municipal health officer; and the laboratory test for the microbial count of selected food service equipment. Phase two was a re-survey of the fastfood personnel to determine the reasons for their compliance, non-compliance to the sanitation code, and their job satisfaction. Results of the study indicated that the customers are knowledgeable about proper foodhandling and their desire is for the fastfoods to comply with the sanitation code. The results of the foodhandlers survey revealed their good knowledge of foodhandling. The survey also showed that they complied with the sanitation code to safeguard the health of the customers. Their primary reason for non-compliance to the code was because they were too busy with other duties. The results also indicated that fastfood personnel were not satisfied with their jobs in the fastfood establishments. In terms of the sanitation check, all the fastfood studied committed violations against the sanitation code. The microbial test indicated that many of the food service establishments did not comply with the safe tolerable limits. The study concluded that the implemented sanitary conditions of fastfood establishments included in the study, were not congruent with the sanitation conditions as prescribed in P.D. 856 and as expected by the customers. It is recommended that fastfood operators be made to comply with what is mandated by the sanitation code. The government health officers should be strict with the enforcement of the sanitation law. It is further recommended that a more comprehensive study be pursued on sanitation practices of other types of food service operations, preferably by the academe. Output from the investigative studies could help in improving the present poor sanitary conditions of the food service operations.